Natural-fiber-reinforced chitosan, chitosan blends and their nanocomposites for various advanced applications - Rushdan, Ahmad Ilyas; Alias, Aisyah Humaira; Nordin, Abu Hassan; Ngadi, Norzita; Mohamed Yusoff, Mohd Zuhri; Muhammad Asyraf, Muhammad Rizal; Salit, Mohd Sapuan; Zainudin, Edi Syams; Sharma, Shubham; Abral, Hairul; Mochamad Asrofi, .; Syafri, Edi; et al. (Multidisciplinary Digital Publishing Institute, 2022)
There has been much effort to provide eco-friendly and biodegradable materials for the next generation of composite products owing to global environmental concerns and increased awareness of renewable green resources. This review article uniquely highlights the use of green composites from natural fiber, particularly with regard to the development and characterization of chitosan, natural-fiber-reinforced chitosan biopolymer, chitosan blends, and chitosan nanocomposites. Natural fiber composites have a number of advantages such as durability, low cost, low weight, high specific strength, non-abrasiveness, equitably good mechanical properties, environmental friendliness, and biodegradability. Findings revealed that chitosan is a natural fiber that falls to the animal fiber category. As it has a biomaterial form, chitosan can be presented as hydrogels, sponges, film, and porous membrane. There are different processing methods in the preparation of chitosan composites such as solution and solvent casting, dipping and spray coating, freeze casting and drying, layer-by-layer preparation, and extrusion. It was also reported that the developed chitosan-based composites possess high thermal stability, as well as good chemical and physical properties. In these regards, chitosan-based “green” composites have wide applicability and potential in the industry of biomedicine, cosmetology, papermaking, wastewater treatment, agriculture, and pharmaceuticals.